Hubungan Pengetahuan, Pendidikan dan Dukungan Keluarga dengan Pemberian ASI Eksklusif - Refi Lindawati (Universitas Faletehan, 2019)
Breastfeeding is an ideal source of nutrition with a balanced composition and adapted to the baby's growth needs. Based on data from the 2012 IDHS, babies who exclusively breastfed up to 6 months were 42 percent. The main causes are low maternal knowledge and lack of family support in breastfeeding. Peucangpari Village is one of the villages in the working area of ​​Cigemblong Health Center, Lebak, Banten, where the coverage of exclusive breastfeeding is still low, which is only 11.9%. The purpose of this study was to determine the relationship between knowledge, education and family support with exclusive breastfeeding. This study is a correlation with a cross sectional approach. The population in this study were mothers who had babies aged 6-24 months in Peucangpari Village, Cigemblong Lebak as many as 42 people, the study sample was taken using a total population technique. The results showed that there was a relationship between knowledge, education, and family support with exclusive breastfeeding in Peucangpari Village, Cigemblong Lebak in 2018. Researchers suggested the need to provide health education to all communities, especially mothers who have babies about the benefits of exclusive breastfeeding, so that the community or mother those who have not given exclusive breastfeeding to their babies can increase their knowledge and will give exclusive breastfeeding to their babies.